Cardiac cycle-induced EPI time series fluctuations in the brain: Their temporal shifts, inflow effects and T 2 ∗ fluctuations - Viessmann, O; Möller, H; Jezzard, P (Elsevier, 2017)
The cardiac-induced arterial pressure wave causes changes in cerebral blood flow velocities and volumes that affect the signals in echo-planar imaging (EPI). Using single-echo EPI time series data, acquired fast enough to unalias the cardiac frequency, we found that the cardiac cycle-induced signal fluctuations are delayed differentially in different brain regions. When referenced to the time series in larger arterial structures, the cortical voxels are only minimally shifted but significant shifts are observed in subcortical areas. Using double-echo EPI data we mapped the voxels’ “signal at zero echo time”, S0, and apparent T2∗ over the cardiac cycle. S0 pulsatility was maximised for voxels with a cardiac cycle-induced timing that was close to the arterial structures and is likely explained by enhanced inflow effects in the cortical areas compared to subcortical areas. Interestingly a consistent T2∗ waveform over the cardiac cycle was observed in all voxels with average amplitude ranges between 0.3-0.55% in grey matter and 0.15–0.22% in white matter. The timing of the T2∗ waveforms suggests a partial volume fluctuation where arteriolar blood volume changes are counterbalanced by changes in CSF volumes.